Ethnobotany Study through the Utilization of Medicinal Plants in Obesi Village, Mollo Utara District, South Central Timor Regency - Angreni Beaktris Liunokas; Nonci Melinda Uki (Jurnal Biologi Tropis, 2020)
The culture of using plants as traditional medicine by a group of local people is always related to regional identity, rituals, and plant diversity that need to be studied in depth. This study is known as ethnobotany study. This study aims to determine, describe, and analyze the level of ethnobotany knowledge of plants in their use as traditional medicine by the Obesi village community, North Mollo district, South Central Timor district. The methods used were surveys and direct interviews which were guided by a list of questions for several Obesi villagers with the snowball sampling technique. The data obtained were presented in tabulated form and analyzed descriptively with a quantitative approach to determine the ethnobotany level of medicinal plants. The results showed that there were 40 types of plants from 28 families that were used by the community to treat various diseases such as rheumatism, appendicitis, hypertension, fever, convulsions, diarrhea, flatulence, and itching with the most used plant parts, namely leaves, fruit, roots/rhizomes, tubers, midrib, bark, and seeds and flowers in a very simple or traditional way. Ethnobotany level of knowledge based on age class is at a moderate level where the lowest (KU1) 0.574 and the highest (KU4) 0.899, and based on gender, women have a higher level of knowledge than men. The research results are expected to be used as a reference source for important information in the utilization of various types of medicinal plants in the surrounding environment.